Effect of Distillation on the Yield and Physico-chemical Properties of Young Nutmeg (Myristica Fragrance HOUTT.) Essential Oil - Djubaedah, Endah; Suriadi, Endang; Moestofa, A.; Basrah Enie, A. (Balai Besar Industri Agro, 1986)
A research on the effects of distillation to the yields and physico-chemical properties of young nutmeg essential oil has been conducted. Fresh and dried nutmeg were distilled by cohobation method for 2, 5, 8, 11, and 14 hrs. The optimum yield of fresh and dried nutmeg essential oil were 15.8% (14 hrs.distillation) and 14.6% (11 hrs.distillation), respectively. The evaporation residues of both oils were increased from ca. 0.25% (2 hrs. distillation)to ca. 0.54% (14 hrs.distillation). Fresh nutmeg essential oil has a highest ester value (6.73 mg/g) and myristic content (17.25%) after 8 hrs.distillation.